Unveiling the Sugary Secrets of Plasmodium Parasites - Goerdeler, Felix; Seeberger, Peter H.; Moscovitz, Oren (Frontiers in Microbiology, 2021)
Plasmodium parasites cause malaria disease, one of the leading global health burdens for humanity, infecting hundreds of millions of people each year. Different glycans on the parasite and the host cell surface play significant roles in both malaria pathogenesis and host defense mechanisms. So far, only small, truncated N- and O-glycans have been identified in Plasmodium species. In contrast, complex glycosylphosphatidylinositol (GPI) glycolipids are highly abundant on the parasite’s cell membrane and are essential for its survival. Moreover, the parasites express lectins that bind and exploit the host cell surface glycans for different aspects of the parasite life cycle, such as adherence, invasion, and evasion of the host immune system. In parallel, the host cell glycocalyx and lectin expression serve as the first line of defense against Plasmodium parasites and directly dictate susceptibility to Plasmodium infection. This review provides an overview of the glycobiology involved in Plasmodium-host interactions and its contribution to malaria pathogenesis. Recent findings are presented and evaluated in the context of potential therapeutic exploitation.